2015
DOI: 10.1097/lgt.0000000000000051
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of At-Home Self-Sampling for HPV Testing as an Appropriate Screening Strategy for Nonparticipants in Switzerland

Abstract: The Self-HPV was accepted by nonattendees of cervical cancer screening programs. Self-sampling may promote screening among the unscreened and underscreened population of women in Switzerland while overcoming some practical barriers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 19 publications
3
26
0
Order By: Relevance
“…This result demonstrates the feasibility of self-collection among Hopi women. As in other studies, most women reported positive attitudes toward self-sampling [6, 8, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40], with almost all reporting that the test was easy to use, and that they would recommend it to a friend or relative. A minority reported discomfort.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…This result demonstrates the feasibility of self-collection among Hopi women. As in other studies, most women reported positive attitudes toward self-sampling [6, 8, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40], with almost all reporting that the test was easy to use, and that they would recommend it to a friend or relative. A minority reported discomfort.…”
Section: Discussionsupporting
confidence: 72%
“…Most previous studies have also reported that a majority of participating women preferred self-sampling [6, 8, 24, 25, 27, 29, 30, 31, 35, 36, 37, 38], although some have returned the opposite finding [26, 28, 34, 39]. In our study, a higher proportion of women who were not adherent to Pap screening, relative to adherent women, preferred self-testing over clinician testing.…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…Our results indicate that self-collecting cervical samples with a standard cytology broom is acceptable to the overwhelming majority of women presenting for care in this context. A similarly high level of acceptability for self-sample HPV testing has been reported in other populations of screening non-attendees [31][32][33][34][35][36], reinforcing the potential of this strategy to increase cervical cancer screening coverage among women at highest risk for developing the disease.…”
Section: Discussionmentioning
confidence: 71%
“…One way to overcome these barriers is by offering women reimbursement for the Pap smear (which costs between 50 and 70 FRS every 3 years), thereby overcoming the financial barrier, Another option is to offer women a self-sampling HPV test kit (self-HPV), which has been shown to be an acceptable screening strategy in Switzerland for most nonresponders. 26 In any case, cervical screening should be a free service. Self-HPV may partly resolve the organizational barriers and, therefore, may increase participation rates in cervical screening.…”
Section: Discussionmentioning
confidence: 99%